Plastics additives an industrial guide - Flick, Ernest W. (Noyes, 1993)
This second edition describes almost 4,000 plastics additives which are currently available to industry. It is the result of information received from 164 industrial companies and other organizations. The data represent selections from manufacturer's decriptions.
Includes index.
Keywords: Plastics -- Additives.; elektronické knihy; electronic books